2010
DOI: 10.1007/s11069-010-9529-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in acid and some heavy metal composition of rainwater harvesting in the oil-producing region of Nigeria

Abstract: The study adopted the experimental research design and field survey of the oil-producing region of Nigeria for the past 10 years. A total of 100 sterilized rain gauges were randomly distributed on the basis of 50 each to the eastern and western division of the oil company operating in the region. The rainwater samples harvested through this process were transferred into sterilized plastic containers and kept in coolers and taken immediately to the laboratory for analysis soon after every rain event. The rainwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Chemical species and their concentration in rainwater are results of the various activities and conditions the atmosphere is subjected to. This is mostly as a result of man-made activities and land use activities (local source) in the area (Efe 2010;Oden 1976). …”
Section: Introductionmentioning
confidence: 99%
“…Chemical species and their concentration in rainwater are results of the various activities and conditions the atmosphere is subjected to. This is mostly as a result of man-made activities and land use activities (local source) in the area (Efe 2010;Oden 1976). …”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the concentrations of Pb and Cd were above the permissible limits at all investigated sites during both seasons. Regarding to sites, the high level of Pb was found at QR site during both seasons, this could be due to conventional oil production activities which taking place at this site and emission of heavy metals, particularly Pb come from combustion of natural gas used in crude oil separators, venting and flaring operations (Efe, 2010), in addition to fossil fuel burning of equipment's and automobiles, while the highest level of Cd was found at NS site, which at this site exist power generation station (Najibiya Station), in which the process and production of power require a substantial amount of energy supplied by fossil fuel burning, as well as traffic activities in the station (Carreras and Pignata, 2002;Banatet et al, 2005). The Cr level during the rainy season was exceeded permissible limits only at NS and QR sites, during the dry season at NS, QR, AK and HW.…”
Section: Total Heavy Metalsmentioning
confidence: 93%
“…These communities depend on such water resources for their only source of drinking water [6]. Studies indicate that acid rain is widely distributed in the Niger Delta region [52][53][54][55]. On average, a pH value of 5.06 from a range of 4.98-5.15 [56] is usually obtained.…”
Section: Water Qualitymentioning
confidence: 99%